Exploring the front squat - Bird, S. P.; Casey, S. (Strength and Conditioning Journal, 2012)
This article explores the "front squat" (fsq) and its variations as part of the "big three" (deadlift, power clean, and squat) exercises prescribed by strength and conditioning coaches to develop total body strength, targeting the hip extensors (gluteus maximus), knee extensors (quadriceps), knee flexors (hamstrings), and core musculature (erector spinae, quadratus lumborum, obliques, rectus, and transverse abdominis). More specifically, the purpose of this article is to introduce strength and conditioning coaches to the fsq teaching progression, with specific emphasis on developing the correct body positioning required for execution of the fsq.